Social and emotional complications in a clinical trial among adolescents with diabetes mellitus. Issue 6369 (19th March 1983) - Kinmonth, A L; Lindsay, M K; Baum, J D
Abstract : Observations are reported on the social and emotional events occurring among children with diabetes mellitus and their families while taking part in a demanding clinical trial. Participants were selected on the basis of: (1) age over 10 years, (2) "informed consent, " (3) cooperation with diabetic care, and (4) family stability. Despite endeavours to apply these criteria, it subsequently emerged that one father had doubts about his daughter participating; one family was suffering from severe marital discord; a girl (11 years) and a boy (10 years) were unexpectedly distressed by the venepunctures required; and another girl (13 years) was falsifying the results of her urine tests. All the families wished to complete the trial, and only one did not because of recurrent hypoglycaemia. The psychosocial problems encountered during the trial were unpredictable and occurred despite selection. Documentation of these problems allowed appropriate emotional support to be offered to the children and their families and provided for a fuller and more reliable interpretation of the trial results than would have been possible from the numerical data alone.